Red Platoon [large type] : a true story of American valor - Romesha, Clinton (Center Point Large Print, 2016)
A first-hand account of the thirteen-hour firefight at Command Outpost Keating describes the events of the October 3, 2009 attack and how the sacrifices of heroic men raised questions about whether the strategically vulnerable outpost should ever have been built.